Kepemilikan Manajerial Sebagai Pemoderasi Pengaruh Capital Intensity Pada Agresivitas Pajak - Budiadnyani, Ni Putu (E-Jurnal Akuntansi; Vol 30 No 9 (2020)DO - 10.24843/EJA.2020.v30.i09.p06, 2020)
This study examines the effect of capital intensity on tax aggressiveness and tests the ability of managerial ownership as a moderating variable on the relationship of the effect of capital intensity on tax aggressiveness. The number of samples analyzed was 34 samples of manufacturing companies in the consumer goods sector which were listed on the Indonesia Stock Exchange (IDX) for five years. The sampling method is nonprobability with a purposive sampling technique. The analysis technique used is linear regression and Moderated Regression Analysis (MRA). The analysis shows that capital intensity has a positive effect on tax aggressiveness. Managerial ownership weakens the effect of capital intensity on tax aggressiveness. Keywords: Capital Intensity; Aggressiveness; Managerial Ownership.